Analisis Kekuatan Rangka Pada Mesin Transverse Ducting Flange (TDF) Menggunakan Software Solidworks - Eko Prasetyo; Rudi Hermawan; Muhammad Naufal Ibnu Ridho; Istihara Ibnu Hajar; Hasan Hariri; Erlanda Augupta Pane (Rekayasa, 2020)
In the industrial world, companies are required to be more effective and creative with the development of today's technology. Transverse ducting flange (TDF) machine is a machine that functions to make ducting flange products and form ducting connections, where there are several components in large quantities, so the design of the frame construction made must be strong to support these components. Responding to the cases that occurred, with the aims and objectives of this study, namely to determine the level of efficiency in the use of the design on a hollow galvanized steel frame measuring (100 × 50 × 3,2) mm, by performing simulations using SolidWorks Premium 2019 software with static analysis features. using the finite element method. So with this research, we can find out whether the frame is receiving loads that exceed the yield strength limit or vice versa. The results of the research are three load-bearing areas received, with load values in a row, namely 11693,809 N, 266 N, and 598,206 N. From the results of the three, it shows that the design of the frame construction that has been made is safe to use, because the calculation of the analysis meets the value requirements safety factor and the maximum stress simulation that occurs does not exceed the yield strength limit of the frame material.